Air, Air Everywhere‑ A Rare Entity - Gazal Singla; Shikha Sood; Sanjeev Sharma (Journal of Digestive Endoscopy, 2018)
Upper gastrointestinal (GI) endoscopy is a widely used diagnostic and therapeutic procedure. Gastric perforation causing pneumothorax, pneumomediastinum, pneumoperitoneum, pneumorrhachis, and subcutaneous emphysema after upper GI endoscopy is an extremely rare complication. We present an interesting case of a 58‑year‑old male who presented to the Emergency Department with recurrent vomiting, abdominal pain and diffuse swelling over abdomen, chest, neck bilateral arms, and thighs after undergoing an endoscopy for a gastric mass.